East Java’s Gerbangkertosusila National Strategic Area’s Economic Structure - Akhmad Jayadi; Fahrizal Taufiqqurrachman (Gorontalo Development Review, 2023)
In order to gain a general understanding of the dominant industries in each district or city and assess the degree of inequality in the area, this paper will analyze the economic structure in the Gerbangkertosusila National Strategic Area using a quantitative research methodology. The three techniques used to analyze the data—Location Quotient, Klassen Typology, and Williamson Index—are all taken from the Central Bureau of Statistics. The results of data processing from the three methods show that the level of inequality between regions is still high and the gap has increased every year. Bangkalan Regency is the only district that is lagging behind in terms of regions that are still in quadrant IV, and there are 10 and 17 business fields that are categorized as underdeveloped. This indicates that the existence of the Suramadu bridge has not been able to have a positive impact on the economy in Bangkalan, which is the gateway to Madura.